FEAR OF CRIME IN ISTANBUL CITY CENTER - Funda Yirmibesoglu; Nilgun Ergun (European Regional Science Association (ERSA), 2011)
The mapping of crime and delinquency has been around for many years and the idea that delinquency is caused by environmental factors has long been debated. A significant characteristic of research on criminality is the use of charts and maps to show spatial distributions of delinquency and crime. Istanbul has been a strategically important location, physically and regionally, in every period. Istanbul's most prominent characteristics are its geographical location, unique natural beauties, and wealth of cultural heritage. Istanbul has experienced increasingly high crime rates. This study demonstrates major differences between the characteristics of high and lower-crime neighbor-hoods in Istanbul. The distribution of crime in Istanbul shows that between 2000-2005, crime is concentrated in the city centre. This research is based on the differences in physical, demographical and economical characteristics of Istanbul's districts, which show a rise of ratios in crime, especially in the city center like Beyoglu and Eminonu districts. In the Beyoglu central district which is economically better developed and with mixed land usage, differentiation of day-night population will be analyzed in order to determine how they could affect increase in crime. The crime survey is conducted in the Beyoglu district between 2006 and 2008. The questionnaire results provide an insight into the mapping of crime in Beyoglu streets. The purpose of the study with this questionnaire is also to analyse fear of crime in the Beyoglu streets. At the end of the research, crime prevention strategies are going to be improved and new suggestions will be presented for the streets where crime rates are high.
Keywords: 330